Priority Directions of development of design of clothing and them practical application in the conditions of present time - Diachenko, A. (Theory and practice of design, 2017)
The article examines the priority areas of fashion design at the Ukrainian fashion market. It was determined that Ukrainian fashion industry priorities of fashion design is kezhual, ethnic, design and business clothes. It was found that the development of fashion design is possible if the quality of the prymirok, presentations, fashion collections, cooperation with the media, communication designer duties artist and designer fashion. Showing practical application areas of fashion design in today’s conditions. We study the priority directions of design activity in Ukraine in terms of post-industrial society and governmental factors that may affect the future direction of design activity; addresses a number of significant obstacles to the development of design in Ukraine.